Unmanned aerial vehicle transport of frozen blood samples using phase change materials. (September 2022) - Ong, Jian Wern; Abid, Hassan A.; Minifie, Tristan; Lin, Eric Shen; Song, Zhixiong; Katariya, Mayur; Liew, Oi Wah; Ng, Tuck Wah
Abstract : Appropriate cryopreservation of blood samples during transit from the point of collection to testing sites is an important element of quality sample management in clinical and veterinary diagnostics and research. Here, a heat-insulated design that employs 23.3% w/w salt water as the phase change material (PCM) for encapsulating a 1.5-mL vial of frozen blood sample was studied to assess its efficacy in maintaining sub-zero temperatures during transport. A two-dimensional finite element numerical simulation model with 5457 elements was found to exhibit mesh independence with 10% convergence error. For the PCM pre-cooled in dry ice and vial sample kept initially at 20 °C before flight, this model is predicted to maintain a stable transport temperature of −20 °C for at least 70 min. It also predicted to have uniform temperature distribution across the PCM holder, PCM, sample vial and sample. Experimental data obtained using a thermocouple confirmed the accuracy of the simulation model. Sensor data collected from a bespoke unmanned aerial vehicle (UAV) allowed mapping of the acceleration forces during flight and facilitated the development of a mechanical setup to experimentally show that frozen samples are protected from shear forces generated under mimicked transport conditions. The capability of real-time sample temperature monitoring with feedback control on UAV flight path demonstrates the viability of the drone delivery system for quality transport of thermal-sensitive samples. Graphical abstract: Image 1 Highlights: UAV transport of frozen blood samples done here with salt water phase change material. 2D finite element model achieved mesh independence with 10% convergence error. 70 min stable transfer at −20 °C attained after 30 min of dry ice pre-cooling. Sensor data from UAV mimicked the flight conditions in a sloshing test setup. Preliminary tests with frozen sheep's blood show lower coagulation from sloshing.